Effect of competitive psychological climate on unethical pro-team behavior: The role of perceived insider status and transformational leadership - Irangani, Sadarika B.K.; Liu, Zhiqiang; Kumar, Nilesh; Khanal, Saroj (Zielona Góra: Faculty of Economics and Management Press)
The purpose of this study is to explain why employees in financial companies in Sri Lanka are likely to engage in unethical pro-team behaviors and how transformational leaders involve controlling unethical pro-team behaviors in a competitive work environment.
Keywords: competitive psychological climate; transformational leadership; perceived insider status; unethical pro-team behaviors; konkurencja; lider; rola liderów; status w zespole; zachowania nieetyczne